2010
DOI: 10.15193/zntj/2010/71/063-072
|View full text |Cite
|
Sign up to set email alerts
|

Content of Nutrients and Minerals, a Nd Fatty Acid Profile in Some Fish Flesh Depending on Fishing Period

Abstract:  ZAWARTOŚĆ SKŁADNIKÓW ODŻYWCZYCH, MINERALNYCH I PROFIL KWASÓW TŁUSZCZOWYCH W MIĘSIE WYBRANYCH GATUNKÓW RYB W ZALEŻNOŚCI OD TERMINU ODŁOWUS t r e s z c z e n i e Badaniami objęto 4 gatunki ryb słodkowodnych: szczupak (Esox lucius L.), sandacz (Sander lucioperca L.), karp (Cyprinus carpio L.) i leszcz (Aramis brama L.), odławianych po 6 sztuk w odstępie miesięcz-nym, od września do listopada 2007 roku. Oceniono cechy morfometryczne ryb oraz zawartość składni-ków odżywczych, mineralnych i profil kwasów tłuszczow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
1
10
2
Order By: Relevance
“…Comparison of the content of Cd in fishery products measured in the present study shows that the maximum content measured by other authors, based on research carried out in various countries (Table 5), was higher than that determined by the present authors; however, some authors obtained lower results [25]. The results of the present authors obtained for Pb were generally higher than those presented by other authors (Table 5).…”
Section: Discussioncontrasting
confidence: 55%
“…Comparison of the content of Cd in fishery products measured in the present study shows that the maximum content measured by other authors, based on research carried out in various countries (Table 5), was higher than that determined by the present authors; however, some authors obtained lower results [25]. The results of the present authors obtained for Pb were generally higher than those presented by other authors (Table 5).…”
Section: Discussioncontrasting
confidence: 55%
“…The mean body weight and length were 2.47 ± 0. 22 As for the fish analyzed in this study, a fat content (%) in the muscle tissue was 10.84 ± 2.98 for Siberian sturgeon, 9.42 ± 2.21 for bighead carp, 3.33 ± 1.83 for wels catfish, and 3.07 ± 0.63 for grass carp. According to the Polish Standard [27], Siberian sturgeon and bighead carp were fat fish, while wels catfish and grass carp were medium fat fish.…”
Section: Resultsmentioning
confidence: 65%
“…Badiani et al [29] showed a higher SFA level in sturgeon (25.99%). Four fish species discussed in this study contained less SFA compared to other freshwater fish species like pike, zander, bream, tilapia, and pangasius, whose SFA level was between 36.28% and 42.18% [22,30]. Palmitic acid (C16:0) was the dominant SFA in the analyzed fish, from 10.50% in wels catfish up to 24.66% in grass carp, contributing 64.34%-78.61% of the total saturated fatty acid (SFA).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The distribution of metals in fish body varies between fish species, depending on sex, age development, and other physiological factors such as salinity, pH, hardness, and temperature [1,2,4,[7][8][9][10][11]. Concentrations of metals in fish tissues can reflect their previous exposures on to pollution.…”
mentioning
confidence: 99%